2015
DOI: 10.1007/s12070-015-0869-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hearing Impairment in High Risk Infants

Abstract: Hearing impairment is prevalent in the general population, early intervention facilitates proper development. The aim of this study was to establish the prevalence of hearing impairment in high-risk infants born between 2013 and 2014. 100 newborns were evaluated using evoked otoacoustic emissions and distortion produce and auditory behavior. Tests were reported if the results were altered. If altered results persisted, the child was referred for impedance testing and when necessary for medical evaluation. Infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…[1][2][3] In our study, we found a prevalence 6.76% (n = 42) of hearing impairment among high risk infants. Our findings were similar to John et al (6.4%) and Gouri et al (5.30%).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…[1][2][3] In our study, we found a prevalence 6.76% (n = 42) of hearing impairment among high risk infants. Our findings were similar to John et al (6.4%) and Gouri et al (5.30%).…”
Section: Discussionsupporting
confidence: 54%
“…Various studies have reported a prevalence of hearing impairment ranging from 0.09 to 2.3% in normal neonates and 0.3 to 20.68% in high risk infants. [1][2][3] In 1999, the American Academy of Pediatrics (AAP) advocated Universal screening of newborn hearing before 3 months and remedial measures, to maximize linguistic and communicative competence and literacy development for hearing impaired children. 4 The Joint Committee on Infant Hearing (JCIH) has also proposed necessary guidelines and the risk indicators, which can be locally adapted to identify infants at risk.…”
Section: Introductionmentioning
confidence: 99%
“…Vasistha et al found prevalence of unilateral and bilateral hearing loss to be 7% and 8% respectively. 6 Riper et al reported a predominance of bilateral hearing loss. 7 However, Meyer et al reported almost equal incidence of unilateral (3.2 %) and bilateral (2.05 %) hearing loss.…”
Section: Resultsmentioning
confidence: 99%
“…Medical College, Ajmer, between 2013 and 2014, found a staggering prevalence of unilateral and bilateral hearing loss of 150 per thousand. 11 A study by Regina et al on 613 high-risk neonates discharged from NICU of Academy of Medical Sciences, Kannur, Kerala, and Sri Siddhartha Medical College and Research Centre, Tumakuru, Karnataka, between August 2015 and August 2016 based on behavioral audiometry, OAE, and auditory brainstem response (ABR) found 42 cases of hearing impairment, representing prevalence of 67.6 per 1,000 neonates. 12 Study on neonates admitted to the NICU at Nemazee Hospital, Shiraz University of Medical Sciences, between January 2006 and January 2007 shows higher prevalence of hearing loss in newborns with a gestational age of less than 36 weeks.…”
Section: Need Of Study: Importance Of Early Detectionmentioning
confidence: 99%